ESG, Intellectual Capital, and Firm Value: The Mediating Role of Profitability in Indonesian Banking - Sharen, Yokazio; Ramadhan, Muhammad Fikri; Sari, Fitri Indah Mayang (Universitas Sulawesi Barat, 2025)
This study focuses on examining the role of profitability in explaining the relationship between Environmental, Social, Governance (ESG) and Intellectual Capital on firm value. The research was conducted on banking sector companies listed on the Indonesia Stock Exchange (IDX) during the 2019–2023 period, with a total sample of 47 companies. Data analysis was carried out using the SPSS version 23 application. The results show that ESG and Intellectual Capital have a significant effect on profitability. However, ESG does not have a significant effect on firm value, while Intellectual Capital and profitability have a significant positive effect on firm value. Furthermore, the findings indicate that profitability is able to mediate the relationship between ESG and firm value, but it cannot mediate the relationship between Intellectual Capital and firm value. These results suggest that the implementation of ESG practices contributes to enhancing firm value through improved profitability, whereas the effect of Intellectual Capital on firm value tends to occur directly without the mediating role of profitability